Microstructural, magnetic and dielectric properties of Bi1-xSmxFeO3 multiferroic materials - Rusly, Siti Nor Ain (2013)
BiFeO3 (BFO) is a most common type of multiferroic materials that exhibits antiferromagnetic and ferroelectric order at room temperature. Based on previous reports, it was rather difficult to synthesize BFO in form of pure single phase due to narrow range of temperature stabilities. Hence, in this thesis, we report some research findings on the effect of different small ranges of calcinations and sintering temperature for preparing BFO. The best BFO sample could be determine by analyzing the phase transformation, magnetic and dielectric properties using XRD, VSM and impedance analyzer respectively. The effect of Sm substitution in the BFO system also has been studied. Samples of Bi1-xSmxFeO3 (BSFO) with x = 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5 were prepared using solid state reaction method. There are three series of samples that have been prepared which are Sample A (both calcinations and sintering temperature at 800 ºC), Sample B (calcinations temperature at 800 ºC and sintering temperature at 825 ºC) and Sample C (both calcinations and sintering temperature at 825 ºC). The XRD pattern showed an improvement of crystallinity in pure BFO with the lower unwanted secondary phases by increasing the calcinations and sintering temperature at 825 ºC. However, the unwanted secondary phases disappeared in BSFO sample implying that Sm3+ substitution can stabilize the perovskite structure. SEM micrograph showed a well defines grain structures with clear grain boundaries in BFO sample. A larger grain sizes were observed as the calcinations and sintering temperature increase. However, BSFO have smaller average grain size than BFO sample. As the Sm composition increases from x = 0.0 to x = 0.5, the density values decreased for all series. The density increases proportionally with sintering temperature caused by elimination pores. The magnetization analysis showed that BFO compound have very narrow hysteresis loop exhibits antiferromagnetic behavior (Hc = 191 Oe and Mr = 1.81 x 10-3emu/g) at room temperature. The result showed magnetic properties were enhanced with higher calcinations and sintering temperature at 825 ºC. Larger hysteresis loop were obtained in BSFO indicates weak ferromagnetic behavior and the magnetization values increases when Sm composition increases. Sample C5 have highest magnetic properties with Hc = 3589.9 Oe and Mr = 7.52 x 10-2 emu/g. The dielectric permittivity, ε and dielectric loss, ε' decreased with increasing of frequency. The higher calcinations and sintering temperature, Sample C has the higher value of ε' and ε''. The value of ε' and ε'' increased with Sm composition and dielectric measuring temperature. The dispersion of ε' and ε'' are maximum for Sample C5 with ε' ~ 141 and ε'' ~ 5 at room temperature. Hence BSFO with x =0.5 with higher calcinations and sintering (825 ºC) is formed to be a better multiferroic material than pure BFO sample by resulting enhancement in magnetic and dielectric properties.